2022
DOI: 10.3390/ijms23116219
|View full text |Cite
|
Sign up to set email alerts
|

Genome–Wide Identification and Functional Characterization of Auxin Response Factor (ARF) Genes in Eggplant

Abstract: Auxin response factors (ARFs) are important plant transcription factors that are differentially expressed in response to auxin and various abiotic stresses. ARFs play important roles in mediating plant growth and stress responses; however, these factors have not been studied in eggplants. In this study, genome–wide identification and the functional analysis of the ARF gene family in eggplants (Solanum melongena L.) were performed. A total of 20 ARF (SmARF) genes were identified and phylogenetically classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…The results revealed that all ARF proteins were classified into 6 subfamilies, with Group IIId consisting solely of AtARFs. This finding is consistent with previous studies on ARF genes in poplar [ 62 ], and eggplant ( Solanum melongena ) [ 63 ], suggesting significant changes in the functions of AtARF family members in Group IIId during species evolution. Group II contained the highest number of ARF genes from Korean pine and Populus (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The results revealed that all ARF proteins were classified into 6 subfamilies, with Group IIId consisting solely of AtARFs. This finding is consistent with previous studies on ARF genes in poplar [ 62 ], and eggplant ( Solanum melongena ) [ 63 ], suggesting significant changes in the functions of AtARF family members in Group IIId during species evolution. Group II contained the highest number of ARF genes from Korean pine and Populus (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…This result indicates that the MsARF family proteins have better hydrophilicity. As transcription factors, ARF proteins usually function in the nucleus [ 7 ]. Consistent with the subcellular localization results reported in other species, such as eggplant [ 7 ], tomato [ 46 ], and maize [ 41 ], the subcellular predictions indicate that most of the MsARF genes were localized to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…As transcription factors, ARF proteins usually function in the nucleus [ 7 ]. Consistent with the subcellular localization results reported in other species, such as eggplant [ 7 ], tomato [ 46 ], and maize [ 41 ], the subcellular predictions indicate that most of the MsARF genes were localized to the nucleus. In addition, no MsARF genes were found to have any conducting peptides, signal peptides, or transmembrane structures, indicating that the 50 MsARF genes located in the nucleus did not secrete or transport but only regulated gene expression in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations